Storming heaven - Brown, Dale, 1956- (Putnam, 1994)
A notorious drug dealer--Henri Cazaux--declares war on the United States and attacks Los Angeles airport from the air, killing thousands. Lieutenant General Robert Blocker is given command of a task force to destroy Cazaux. By the author of Chains of Command.